2014
DOI: 10.17795/ajdr-21046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Manual and Electric Toothbrush in Dental Plaque Removal: A Clinical Trial

Abstract: Background: Mechanical oral hygiene procedures are the most effective means of plaque removal and toothbrush is the most commonly used tool for mechanical plaque removal worldwide. There is an array of available manual and electric toothbrushes in the market. Thus, choosing the best one for dental plaque removal can be of great help for patients. Objectives: This study aimed at compare the efficacy of dental plaque removal using a manual and an electric toothbrush. Materials and Methods:This experimental, sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Another study reported a significant difference in the intergroup comparison of the baseline and follow-up plaque index for the orthodontic toothbrush [ 30 ]. In some studies, the improvement in the plaque reduction of the orthodontic toothbrush compared to conventional toothbrushes was not statistically relevant [ 26 , 35 ]; however, there was no report of worsening oral health during re-evaluations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported a significant difference in the intergroup comparison of the baseline and follow-up plaque index for the orthodontic toothbrush [ 30 ]. In some studies, the improvement in the plaque reduction of the orthodontic toothbrush compared to conventional toothbrushes was not statistically relevant [ 26 , 35 ]; however, there was no report of worsening oral health during re-evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies have reported clinically significant plaque reductions with the Pulsar brush on intact teeth [ 19 - 21 ]. Some studies have compared the Pulsar toothbrush with the powered brushes and did not find a statistically significant difference between the two brushes [ 35 ]. The better performance has been attributed to the special features of this brush, as well as the pressure-sensitive split head that conforms to the contours of the teeth to clean the difficult areas and moderately hard surfaces and maintains a moderate amount of pressure on the teeth and gums.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical trials have shown that there is no difference in plaque removal between MTBs and ETBs when proper techniques are followed. In one study, subjects had their teeth brushed by a periodontist [ 39 ] and, in another study, trained dental students were the study subjects [ 37 ]. However, brushing performed by dental professionals is not representative of the brushing practice performed by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, no additional interdental oral hygiene tools were recommended. Re et al 5 , Silvermann et al 19 , Sheikh-Al-Eslamian et al 18 used the same index to record the dental plaque. Yousaf et al 3 studied with Silness-Löe plaque index, because it can be recorded easily and evaluated in a simple way.…”
Section: Discussionmentioning
confidence: 99%